A mathematical model for HIV prevention and control among men who have sex with men in China. (2020) - Lu, Z.; Wang, L.; Wang, L. P.; Xing, H.; Fu, G.; Yan, H.; Wang, L.; Li, Z.; Xu, J.; Wang, N.; Wang, K.; Peng, Z.
Abstract: In recent years, men who have sex with men (MSM) constitute a major group of HIV transmission in China. High primary drug-resistance (PDR) rate in MSM also represents a serious challenge for the Chinese antiretroviral therapy (ART) program. To assess the efficiency of ART in controlling HIV/AIDS infection among MSM, we developed a compartmental model for the annually reported HIV/AIDS MSM from 2007 to 2019 in the Zhejiang Province of China. R0 was 2.3946 (95% CI (2.2961–2.4881)). We predict that 90% of diagnosed HIV/AIDS individuals will have received treatment till 2020, while the proportion of the diagnosed remains as low as 40%. Even when the proportion of the diagnosed reaches 90%, R0 is still larger than the level of AIDS epidemic elimination. ART can effectively control the spread of HIV, even in the presence of drug resistance. The 90-90-90 strategy alone may not eliminate the HIV epidemic in Chinese MSM. Behavioural and biologic interventions are the most effective interventions to control the HIV/AIDS epidemic among MSM.